Epidemiology of pyoderma gangrenosum: Results from an Italian prospective multicentre study. Issue 6 (6th June 2018) - Monari, Paola; Moro, Ruggero; Motolese, Alberico; Misciali, Cosimo; Baraldi, Carlotta; Fanti, Pier Alessandro; Caccavale, Stefano; Puviani, Mario; Olezzi, Daniela; Zampieri, Pierfrancesco; Trevisan, Giusto; Nan, Katiuscia; et al.
Abstract : Pyoderma gangrenosum (PG) is a neutrophilic dermatosis characterised by painful, necrotic ulcerations. PG is described as a rare disease: the world‐wide incidence is estimated to be around 3 to 10 cases per million population per year. These estimations are based mostly on case reports and retrospective case series; there are no prospective, multicentre studies on the matter. The apparent rarity of PG is in contrast with our clinical perception as dermatologists: in our opinion, PG is not so uncommon. Therefore, we decide to investigate the epidemiology of PG in the Italian population and confirm our clinical suspicions that it is not an orphan disease. We enrolled all patients diagnosed with PG in 8 Italian Dermatological Departments from 1st October 2014 to 1st November 2015, and we recorded their features. Our data, collected from 64 patients, are in accordance with those of the published literature regarding the epidemiology and features of PG. In an Italian population of roughly 8 million inhabitants of 7 provinces, we found an incidence of 5.17 new cases per million population per year. Unlike our predictions before the study, we confirmed the world‐wide incidence of PG. To our knowledge, this is the first observational, multicentre study on PG. We hope that it provides a stimulus for further researches on PG and for the creation of an Italian register.